The expression of information structure - Krifka, Manfred (The expression of cognitive categories, 2012)
The book reports on the present state of the theoretical presentation, empirical investigation, psycholinguistic aspects and acquisition of information structure, and computation. It also provides descriptions of the information structural encoding strategies of individual languages of different types. The book can be used as a textbook appropriate for advanced undergraduate and graduate courses.